Research on Heat Exchanger of Gas Hydrate Mud Cooling System - Zhao Shuai; Sun Youhong; Guo Wei; Jia Rui; Wang Yuan; Chen Guanghu (Zhileng xuebao)
The heat exchanger of the gas hydrate mud cooling system is very critical to the exploitation of gas hydrate. Based on the occurrence characteristics of gas hydrate, the study focused on the effect of different kinds of heat exchanger to the original gas hydrate sample acquired by drilling. Under the same conditions, the heat transfer efficiencies of coaxial heat exchanger and spiral heat exchanger with the same heat transfer area were measured and analyzed. By combining the experimental results with heat transfer calculation and numerical simulation, it indicated that the heat efficiency of spiral heat exchanger was higher than that of coaxial heat exchanger 70% when the conditions required by coring hydrate sample was achieved.